Dampak Perubahan Pengaturan Penataan Ruang Pasca Pengesahan Undang-Undang Cipta Kerja - Arsawan, I Gede Yudi; Yusa, I Gede (Amsir Law Journal, 2023)
This article analyzes the impact of changes to spatial planning arrangements after the promulgation of the Job Creation Act Number 6 Year 2023. This article aims to find out whether the enactment of the Job Creation Act properly accommodates the need for spatial planning arrangements. This article uses a type of juridical-normative legal research with secondary research data in the form of primary legal materials and secondary legal materials. The results of the study found that changes to spatial planning arrangements in the Job Creation Act had the following impacts: the implementation of spatial use can be carried out without a spatial plan for the implementation of strategic national policies, there is a reduction in the authority of the regional government in carrying out spatial planning so that some tasks are carried out by the central government, and there is a reduction in the function of community control, especially regarding the cancellation of environmental permits through the courts. ___ Referensi Buku dengan penulis: Kodoatie, Robert J., & Sjarief, Roestam. (2010). Tata Ruang Air. Denpasar: Penerbit Andi. Riyanto, Sigit., dkk. (2020). Kertas Kebijakan: Catatan Kritis Terhadap UU No. 11 Tahun 2020 tentang Cipta Kerja. Yogyakarta: UGM. Santosa, Deddy Pandji. (2020). Penataan Ruang Melalui Pendekatan Administrasi Publik. Malang: Inteligensia. Sitorus, Santun R.P. (2019). Penataan Ruang. Bogor: PT Penerbit IPB Press. Wahid, A. M. Yunus. (2016). Pengantar Hukum Tata Ruang. Jakarta: Prenada Media. Waskito, dkk. (2018). Pertanahan, Agraria, dan Tata Ruang. Jakarta: Kencana. Artikel jurnal: Baihaki, M. R. (2021). Persetujuan Lingkungan sebagai Objectum Litis Hak Tanggung Gugat di Peradilan Tata Usaha Negara (Telaah Kritis Pergeseran Nomenklatur Izin Lingkungan menjadi Persetujuan Lingkungan Dalam Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja). Majalah Hukum Nasional, 51(1), 1-20. Hamja, B., Aswir, F., & Ahmad, S. (2021). Fungsi Kewenangan Daerah Dalam Perencanaan Tata Ruang di Daerah Perbatasan Kabupaten/Kota. Jurnal Cakrawala Ilmiah, 1(2), 135-146. Helmi, H. (2011). Membangun Sistem Perizinan Terpadu Bidang Lingkungan Hidup di Indonesia. Jurnal Dinamika Hukum, 11(1), 139-148. Imamulhadi, I. (2021). Aspek Hukum Penataan Ruang: Perkembangan, Ruang Lingkup, Asas, dan Norma. Bina Hukum Lingkungan, 6(1), 121-144. Islamuddin, A., & Bima, M. R. (2021). Perbandingan Kewenangan Kepala Daerah Menurut Undang-Undang No 23 Tahun 2014 dan Undang-Undang No 11 Tahun 2020 Tentang Cipta Kerja. Journal of Lex Generalis (JLG), 2(10), 2610-2625. Masayu, N. T. (2021). Implikasi Undang-Undang Cipta Kerja terhadap Kewenangan Pemerintah Daerah dalam Melaksanakan Penataan Ruang Nasional dan Penyelenggaraan Penataan Ruang. Jatiswara, 36(3), 238-249. Mulyani, B. (2020). Dekonstruksi Pengawasan Peraturan Daerah Setelah Berlakunya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja. Juridica, 2(1), 91-113. Purwanda, S., Betaubun, R. M. N., & Rado, R. H. (2023). Klasifikasi Penetapan Daerah Terdepan, Terluar dan Tertinggal (Daerah 3T) Dalam Regulasi Indonesia. Jurnal Komunikasi Hukum (JKH), 9(1), 931-943. Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163. Sutaryono, S., Nurrokhman, A., & Lestari, N. D. (2021). Penguatan Pelaksanaan Penertiban Pemanfaatan Ruang Pasca Terbitnya Undang-Undang Cipta Kerja. Jurnal Pengembangan Kota, 9(2), 154-165. Vilyasari, L., & Saputra, A. (2023). Implementasi Jaminan Kesehatan Pasien di Semarang Berdasarkan Undang-Undang BPJS. Amsir Law Journal, 4(2), 112-119. Widodo, A., Solekhan, M., & Siswanto, B. (2022). Peran Serta Masyarakat Dalam Pengelolaan Lingkungan Hidup di Kota Semarang. Justicia Sains: Jurnal Ilmu Hukum, 7(1), 132-146. Wirasaputri, N. M. (2014). Proses Penyusunan Rencana Tata Ruang Dalam Kaitan Kelestarian Fungsi Lingkungan Hidup. Kanun Jurnal Ilmu Hukum, 16(1), 129-146. World Wide Web: Indonesian Center for Environmental Law (ICEL). (2020). Berbagai Problematika Dalam UU Cipta Kerja Sektor Lingkungan dan Sumber Daya Alam. Tersedia secara daring dari: https://icel.or.id/seri-analisis/berbagai-problematika-dalam-uu-cipta-kerja-sektor-lingkungan-dan-sumber-daya-alam/ . [Diakses 23 Mei 2023]. Tempo. (2020). UU Cipta Kerja: Penataan Ruang oleh Pusat, Tak Lagi Pemda. Tersedia secara daring dari: https://nasional.tempo.co/read/1393656/uu-cipta-kerja-penataan-ruang-oleh-pusat-tak-lagi-pemda . [Diakses 3 Mei 2023].